RESULTS OF A PILOT PROGRAM FOR MONITORING THE RESISTANCE OF Heliothis uirescens (FABRICIUS) TO METILPARATION AND PIRETROIDS IN THE COTTON ZONE OF EL ESPINAL, HARVEST 1988 TO - RENDON, FRANCISCO; SIABATTO, ALFREDO; HERRERA, MIGUEL ANGEL; ALVAREZ-A., GUILLERMO (Revista Colombiana de Entomología, 1990)
The H. virescens resistance to Cypermethin, Fenvalerate, and Methyl Parathion was evaluated through the seedling of 1988 in the cotton area of Espinal, Colombia. The trials were carried over five small areas and three periods in the cultivation. Measuring it in terms of survival with respect to a discriminated class with the capacity of killing between 90% and 98% of a laboratory strain, it was found an increment between the first and the last sampling period for Pyrethroids, although wasn't equal for all the small plots. In all the areas the survival index was stable for Methyl Parathion. For all the areas where the work was done the resistance measured in terms of the LD50 to Fenvalerato and Methyl Parathion shows .the the same level of resistance to that found for the discriminated close and dilution with respect to Methyl Parathion with regard to the LD50 found in 1977/1978. The field samples held to evaluate the natural control factors related to Trichogramma sp, no egg eclosion, and parasitism on larvae by Cardiochiles nigriceps. According to the results of this study, it is recommended to establish a national program of resistance monitoring in order to set up strategies of management that allow extending the [lie work of pyrethroids.